The wars of Afghanistan messianic terrorism, tribal conflicts, and the failures of great powers - Tomsen, Peter (PublicAffairs, 2013)
An insider's account of Afghanistan's history since the 1970s and how the CIA's covert operations and the Pentagon's military strategy have strengthened extremism in the country.